(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Tourism workers finally gave up losing their jobs due to the closure of many tourism companies, returned to their hometowns, switched professions to agriculture, trade, online transportation and other sectors. Since the 1st Bali Bombing (2002), 2nd Bali Bombing (2005), the eruption of Mount Agung up to the Covid 19 Pandemic, there has been no strategy, model or concept set by the Government or the private sector in Bali to anticipate this employment tsunami. Tourism workers need additional skills in the field of Digital Literacy. Strengthening the Digital Literace for Tourism Workers Competence will realize the independence of the Workers. Researchers will try to complement previous research by emphasizing the importance of Digital Literacy which must be owned by every Tourism worker who is equipped with Self-Efficacy abilities for the independence of Tourism workers and is able to have strong Digital Competency to deal with a Dynamic Environment that can change at any time. This study will examine the direct and indirect effects of Digital Literacy on Self-Efficacy and Digital Competence by using the Dynamic Environment moderating variable and expanding the empirical study of Tourism workers on a larger scale. This study uses a grand theory: Self Efficacy Theory, Competence Based Education Theory and Planned Behavior Theory. Total respondents were 270 Tourism staff who were still working or those who were part-time during the pandemic, IT experts and users in 7 Hotels, 5 Villas, 3 Tourism Destinations in Bali.This research is a quantitative research. Multivariate analysis with the application of AMOS-based structural equation models or SEM (structural equation modeling). This research as a practical reference, is expected to be an empirical contribution to Bali Tourism and also useful for other Tourism destinations around the world in dealing with Manpower disaster management and preparedness, with a focus on the Digital Literacy model and Tourism Workers Competence.